WACANA HUMOR DALAM MEME DI MEDIA ONLINE SEBAGAI POTRET KEHIDUPAN SEBAGIAN MASYARAKAT INDONESIA - Listiorini, Ari (LITERA, 2017)
Abstract This study aims to describe themes and topics, implicatures, and language aspects in humor discourse in memes in online media. The study employed the descriptive research design. The data sources were 70 memes in four sites of online meme media, i.e. www. memecomicindo.com,www.indomeme.com, www.memecomic.id, and www.1cak.com. The results of the study are as follows. First, there are four meme themes in online media; they are social, political, legal, and religious themes. Second, there are three implicatures in memes in online media, namely insinuation, suggestion, and the combination of insinuation and suggestion. Third, there are two language aspects that support implicatures and result in humor in memes, namely the phonological and semantic aspects. The phonological aspect includes the repetition of sounds which in literature is often called a rhyme. The semantic aspect comprises the repetition of words and the use of similes, metaphors, hyperboles, personifications, syllogisms, abbreviations, and proverbs. Keywords: themes, topics, implicatures, language aspects, memes